Development of compatible fungal mixed culture for composting process of oil palm industrial waste - Mohammad, Noor; Alam, Md Zahangir; Kabbashi, Nassereldeen Ahmed; Adebayo, Opatokun Suraj (Academic Journals, 2011)
Trichoderma reesei (Tr), Penicillium sp. (P), Basidiomycete M1 (M1) and Panus tigrinus M609RQY (IMI398363)(M6) were tested to find their mutual growth in the laboratory. Potato dextrose agar (PDA) as a media was used for their fifteen combinations and two different fungi were grown 4 cm apart in every combination. The results of this present study showed that the combinations of T. viride and Penicillium sp. (Tv/P), T. viride and Basidiomycete M1 (Tv/M1), T. reesei and P. tigrinus M609RQY (Tr/M6) may interact as compatible, while A. niger and T. viride (A/Tv), A. niger and T. reesei (A/Tr), T.viride and T. reesei (Tv/Tr) and Penicillium sp. And P. tigrinus M609RQY (P/M6) were partially compatible and the other combinations were incompatible or inhibited by each other. Furthermore, the cellulolytic fungus T. viride was the dominant in all its combinations, and its growth rate and hyphal expansion showed the highest responses as compared to all combinations. These compatible filamentous fungi would be useful for effective composting process in further study.